JAPANESE LYRICAL PROSE ON THE EXAMPLE OF ISE MONOGATARI (TALES FROM ISE). - Kordzińska-Nawrocka, Iwona (Porównania, 2016)
The aim of this article is to introduce Ise monogatari (Tales of Ise) – the most outstanding example of the court tales genre called uta monogatari (lyrical prose). Amongst court tales (ōchō monogatari), uta monogatari proves to be an extremely original type of prose, in which the storyline plays a secondary role while the world described is mostly depicted through the poetic re-creation of reality. The element that links all the episodes of Ise monogatari into a whole is the figure of mukashi otoko, “a Man of Old”, implying Ariwara Narihira (825–880), a poet and nobleman. The article presents the main characteristics of the genre, the worldview and social background, the reasons for which this literary work is identified with the beauty of courtly elegance, miyabi.